(untitled) (Al-Qamar, 2021)
It’s a historical fact that Bhutto government introduced a number of reforms for the development of the country. However, as far as concentration of powers and prolonging his rule is concerned, he was no less than a dictator. His concentration of powers in his own person even created differences within his own party. On the other hand, the rapidly increasing inflation and law and order issues particularly the murder of some well-known personalities led to anti-Bhutto sentiments among the people. It was in these circumstances that his political opponents started a propaganda against his governance style. In the start of 1977, Bhutto announced elections before the expiry of the already serving assemblies. The opposition parties formed an electoral alliance called Pakistan National Alliance[1] (PNA). The Alliance consisted of nine parties with a diverse set of ideologies, backgrounds, and political goals. The PNA started propaganda against the governance style of Bhutto and alleged that Bhutto would rig the upcoming elections. Despite the fact that the nine political parties adhered to different socio-political values, a slogan to Islamize the political system of the country was the most common factor among them. Thus, they promised that they will enforce Islamic laws (Nizam-e-Mustafa) and Sharia if came into power. Opposition to the autocratic rule by Bhutto and his party PPP seemed to be the main force holding the otherwise diverse nine political parties together.